Epigenetic regulation of triple negative breast cancer (TNBC) by TGF-β signaling - Radhakrishnan Vishnubalaji (3563306) (2021)
TGFβ signaling plays crucial role during development and cancer, however the role for TGFβ signaling in regulating the noncoding part of the human genome in triple negative breast cancer (TNBC) is still being unraveled. Herein, we provide the transcriptional landscape of TNBC in response to TGFβ activation and subsequent inhibition employing SB431542, selective TGFβ1 Receptor ALK5 Inhibitor. Our data revealed 72 commonly upregulated [fold change (FC) ≥ 2.0], including PLAU, TPM1, TAGLN, COL1A1, TGFBI, and SNAI1, and 53 downregulated (FC ≤ 2.0) protein coding genes in BT-549 and MDA-MB-231 models in response to TGFβ1 activation. Alignment to the geocode (V33) identified 41 upregulated (FC ≥ 2.0) and 22 downregulated (FC ≤ 2.0) long non-coding RNA (lncRNA) in response to TGFβ1 activation, which were inhibited by concurrent treatment with SB431542. To place our data from the in vitro models into their clinical context, we identified AC015909.1, AC013451.1, CYP1B1-AS1, AC004862.1, LINC01824, AL138828.1, B4GALT1-AS1, AL353751.1, AC090826.3, AC104695.4, ADORA2A-AS1, PTPRG-AS1, LINC01943, AC026954.3, TPM1-AS, ZFPM2-AS1, AC007362.1, AC112721.2, MALAT1, AL513314.2, AC112721.1, AC010343.3, LINC01711, and MAP3K2-DT lncRNA expression to positively correlate with TGFβ1 expression in a cohort of 360 TNBC patients. To provide mechanistic insight into lncRNA regulation by TGFβ signaling, SMAD2/3 ChIp-Seq data from BT-549 TNBC model retrieved from Gene Expression Omnibus (GEO) revealed direct binding of SMAD2/SMAD3 to the promoter of AC112721.1, AC112721.2, MALAT1, HHIP-AS1, LINC00472, and SLC7A11, suggesting their direct regulation by TGFβ1/SMAD2/SMAD3 pathway. Interestingly, AC112721.1, AC112721.2 exhibited higher expression in TNBC compared to normal breast tissue suggesting a possible role for those lncRNA in TNBC biology. Our miRNA analysis in the BT-549 model in response to exogenous TGFB1 revealed several affected miRNAs (2.0 ≤ FC ≤ 2.0), whose expression pattern was reversed in the presence of SB431542, suggesting those miRNA as plausible targets for TGFβ regulation. In particular, we observed hsa-miR-1275 to be downregulated in response to TGFB1 which was highly predicted to regulate PCDH1, FIBCD1, FXYD7, GDNF, STC1, EDN1, ZSWIM4, FGF1, PPP1R9B, NUAK1, PALM2AKAP2, IGFL3, and SPOCK1 whose expression were upregulated in response to TGFβ1 stimulus. On the other hand, hsa-miR-181b-5p was among the top upregulated miRNAs in response to TGFB1, which is also predicted to regulate CDKN1B, TNFRSF11B, SIM1, and ARSJ in the BT-549 model. Taken together, our data is the first to provide such in depth analysis of lncRNA and miRNA epigenetic changes in response to TGFβ signaling in TNBC. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-021-94514-9